Africa Yearbook Volume 20 Politics, Economy and Society South of the Sahara in 2023 - Alidu, Seidu (Brill, 2024)
The Africa Yearbook is a reliable source of reference covering major domestic political developments, the foreign policy and socio-economic trends of all sub-Saharan states - all related to developments in one calendar year.
Description based on publisher supplied metadata and other sources